2011
DOI: 10.4103/0259-1162.94758
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between preemptive gabapentin and paracetamol for pain control after adenotonsillectomy in children

Abstract: Background:Tonsillectomy is the most commonly performed surgical procedure in ENT practice. Postoperative pain remains the major problem following tonsillectomy, if not treated. Different methods and many drugs have been used to control the postoperative pain. In this study, we evaluate the role of gabapentin premedication vs paracetamol in management of postoperative pain following adenotonsillectomy in children.Materials and Methods:In a double blind randomized study, 70 children were subjected for adenotons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 14 publications
2
32
1
2
Order By: Relevance
“…Sabry and colleagues have compared the efficacy of pre-emptive gabapentin and paracetamol in adenotonsillectomies [13]. They found premptive gabapentin to be more efficacious compared to paractemol, but unlike our study they used oral paracetamol.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Sabry and colleagues have compared the efficacy of pre-emptive gabapentin and paracetamol in adenotonsillectomies [13]. They found premptive gabapentin to be more efficacious compared to paractemol, but unlike our study they used oral paracetamol.…”
Section: Resultsmentioning
confidence: 59%
“…Intravenous paracetamol has been used as a pre-emptive analgesic in various other surgeries [9,10,13]. Arici and colleagues [9] have found that preemptively administered iv paracetamol 1g in patients undergoing a total abdominal hysterectomy operation had no negative effects on intra-operative or post-operative hemodynamic parameters, ensured an effective analgesia during the post-operative period, increased patient satisfaction by reducing post-operative morphine consumption and side effects, and thereby shortened the length of hospital stay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from eligible studies were extracted using standardized forms and were independently checked by the two reviewers. Outcomes analyzed were postoperative pain (swallowing or resting pain scores after leaving the operation room), 2,6,8-12 postoperative (24 hours) analgesic requirements (either doses or percentage of patient receiving postoperative opioids or nonopioids analgesics), 2,6,[8][9][10]12,13 time to first analgesic administration (opioids or nonopioids analgesics administered with a defined pain intensity target), [9][10][11] time to first oral uptake, 2,5,12,13 the occurrence of postoperative nausea and vomiting (incidence or percentage of patients), 2,6,[8][9][10][11][12][13] dizziness, 6,8,12 and headache, 6,8,12 or sedation (sedation scores). 2,11 These outcomes were compared between the preoperative gabapentinoids group, in which there was intravenous and oral administration, and the control group, in which there was no treatment or use of opioids during the 24-hour postoperative period.…”
Section: Data Extraction and Risk Of Bias Assessmentmentioning
confidence: 99%
“…Adoptamos esta recomendación y así fueron evaluados nuestros pacientes diariamente; 13,25,29 6) usar terapias multimodales para el manejo del dolor (Servicio de Psicopatología y Terapia Física); 7) preferir la VO a la VE; 30,31 también coincidimos con ambas recomendaciones; 8) está recomendada, a nivel internacional, la analgesia por bomba que puede ser administrada por el paciente. 32,33 En nuestro medio, no contamos con esta modalidad ni con la infusión de fármacos por catéter epidural por la necesidad de disponer de Terapia Intensiva para todos nuestros pacientes en el posoperatorio inmediato; 9) incluir paracetamol o a un antinflamatorio no esteroide en el protocolo multimodal de analgesia por el efecto de potenciación de ambos fármacos; 14,17,34 10) administrar pregabalina (150-300 mg/día) o gabapentina (600-1200 mg/día), ambas se asocian con mejores puntajes posoperatorios de dolor y con menores requerimientos de opioides poscirugía, como se administran solo por VO no pueden indicarse en el posoperatorio inmediato; [18][19][20][21]26,27,35 11) promover el desarrollo de políticas y procedimientos estandarizados para la correcta implementación del protocolo de manejo del dolor en el posoperatorio de una cirugía de columna y designar un equipo para su control, a fin de garantizar la implementación del protocolo. 36 Compartimos estos conceptos, las últimas dos recomendaciones serán desarrollados en futuros estudios.…”
Section: Discussionunclassified